RESEARCH OF PHYSICOMECHANICAL AND TECHNOLOGICAL PROPERTIES OF GRAIN IN PROCESSES OF DAMP ROLLING IT FOR A FORAGE OF FARMING ANIMALS, WITH THE PURPOSE OF REVEALING THE DIRECTIONS OF DEVELOPING A POWER-SAVING OPERATING ELEMENTS - D.I. CHISTIAKOV (Advanced Engineering Research)
The research provides a new data about the properties of cultivated environment for developing a power-saving operating elements for grain processing of a farming animal's forage. It received a new quantitative estimations of changing the basic rheological constants of damp grain in processes of rolling, determining their technological and physic mechanical characteristics. Dependences 168 Раздел Инженерно-агропромышленные специальности» between technological modes and structural parameters of operating elements for rolling, suitable for performance engineering are proved.